Strong Convergence Algorithm for Split Equilibrium Problems and Hierarchical Fixed Point Problems - Abdellah Bnouhachem (The Scientific World Journal)
The purpose of this paper is to investigate the problem of finding the approximate element of the common set of solutions of a split equilibrium problem and a hierarchical fixed point problem in a real Hilbert space. We establish the strong convergence of the proposed method under some mild conditions. Several special cases are also discussed. Our main result extends and improves some well-known results in the literature.